The Spanish Mission Church in Central New Mexico: A Study in Architectural Morphology - Hanlon, Don (Anthropologica, 2022)
This paper is a case study of architectural morphology: the emergence of a hybrid form from the fusion of two archetypes, the European Christian church and the Pueblo Indian kiva. The author suggests that, contrary to common perception, the Spanish mission church in the American Southwest is in some important respects formally and spatially more closely related to the kiva than to traditional church forms. The focus of the observations in this study is the family of mission churches in central New Mexico.